Finlayson’s Characteristic of Liberal Feminism in The Woman King (2022) Movie - Putri Bella Anggraeni; Dewi Wulan Sari (Asosiasi Dosen Muda Indonesia, 2025)
Liberal feminism emphasizes freedom between men and women that is balanced and equal without oppression. Liberal feminism refers to the inherent idea of women being subordinate to men in all social spheres. This research aims to find out finlayson’s characteristic of liberal feminism in The Woman King (2022) movie. The researcher used the qualitative method and Finlayson (2016) theory to identify the characteristics of liberal feminism in this research. The researcher found 12 data namely 4 data of individualism, 4 data of distribution, 1 data of abstraction, 2 data of positivity, and 1 data of capitalism. The liberal feminism characteristics in The Woman King (2022) movie were dominated by distribution and individualism.